(untitled) (Journal of actual problems of jurisprudence, 2016)
This article deals with the concept of the principle of justice, as well as some aspects of its implementation during the state tax policy. On the basis of a study of publications of scientists, as well as its own scientific research author examines some aspects of the fairness principle in the fiscal policy conduct. The principle of fair taxation is based on the constitutional norm of equality of all before the law and the courts,is essential to the economic growth of the country. At the same time, in the current Tax Code provides for certain benefits and privileges that are growing constantly and unpredictably. Based on this, the author proposes to concretize the concept of justice in acts of interpretation, and to develop the concept of a tax burden fair distribution, which, based on their own traditions, should encompass the best examples of international practice, guarantee the implementation of constitutional and economic rights and freedoms to citizens.